Cancer Morbidity and Computed Tomography: "After" and "Due to" Challenge - Mikhail Osipov; Vladislav Loginov; Vladimir Melnikov; Viktor Shkarednyh; Polina Druzhinina (Ital Publication, 2021)
The article discusses the problem of carcinogenic risk assessment in the context of relationship with diagnostic radiation resulted from Computed Tomography (CT). The study aimed to evaluate the possible long-term carcinogenic effects after the exposure to a low dose of diagnostic radiation, appeared within a decade after the 1st CT scan. Information on patients examined using CT in the District Hospital of Kasli (KDH) has been derived from the CT archives since 2009 when the first CT examinations has been performed in the KDH. The data were linked to local Cancer registry, the Death registry, and the "CT Registry" database (CTDB) to obtain the information on vital status, the cause of death, cancer morbidity and CT examinations outside KDH, respectively. 275 CT examinations of 246 patients have been recorded to the data file (KDH cluster). To the end of the study, 46 cases of malignant tumours (MT) have been accumulated in the study group. The average observation time was 6.5 years (90% CI 6.2-6.8). The distribution of cancers among patients exposed to CT has been shown retrospectively through the date of birth of patient to December, 31, 2018. The cases of MT diagnosed prior to 1st CT examination have been excluded from the analyses. Cancer-related conditions stated before the date of 1stCT examination have been accounted. The cumulative cancer incidence after the exposure to CT, adjusted for predisposed conditions in the study group was 4.8%. The study results have been compared with the results of the LSS cohort study to assess the expected excess cancer morbidity. The data obtained in the study provide the information for a comprehensive epidemiological assessment of long-term effects related to diagnostic radiation exposure in the Ozyorsk Computed Tomography Cohort (OCTC study).   Doi: 10.28991/SciMedJ-2021-0304-3 Full Text: PDF